FACTORS AFFECTING SOCIAL RESPONSIBILITY DISCLOSURE AND ITS IMPACT ON THE FINANCIAL PERFORMANCE OF COMPANIES LISTED ON INDONESIA STOCK EXCHANGE PERIOD OF 2007-2011 - Prayanthi, Ika; Budidarma, I Gusti Agung Musa (JBE (Journal of Business and Economics), 2014)
This study aimed to examine whether the financial performance, in this case the Return on Asset and Return on Equity, affect the social responsibility disclosure. In addition to that, it also examined whether there is a significant difference on the Return on Asset and the Return on Equity between companies which contrived social responsibility disclosure and companies which did not. The samples of this study consisted of 143 companies, and the data were taken from the Indonesian Capital Market Directory and Indonesian Sustainability Reporting Award. This study utilized the logistic regression and difference testing method. The results from the logistic regression analysis show that there was a significant effect on the Return on Asset towards the social responsibility disclosure, but no significant effect between the Return on Equity on the social responsibility disclosure. When it is being tested together, it was found that only the Return on Asset had a significant effect on the social responsibility disclosure. The results from the difference testing through independent sample T Test indicated that there was a significant difference on both the Return on Asset and the Return on Equity between the companies which contrived social responsibility disclosure and the companies which did not. The mean score of the Return on Asset and the Return on Equity of companies which contrived the social responsibility disclosure was greater compared to the companies which did not contrive the report. This study also found that one year after social responsibility disclosure was made, the companies’ financial performance decreased, but in three consecutive years of the study period, the average performance of the companies that contrive social responsibility disclosure report showed progress of significant improvement.